2014
DOI: 10.1016/j.fm.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of Salmonella enterica serovar Enteritidis from poultry house and clinical samples during 2010

Abstract: b s t r a c tA total of 60 Salmonella enterica serovar (ser.) Enteritidis isolates, 28 from poultry houses and 32 from clinical samples, were isolated during 2010. These isolates were subjected to testing and analyzed for antibiotic resistance, virulence genes, plasmids and plasmid replicon types. To assess genetic diversity, pulsed-field gel electrophoresis (PFGE) fingerprinting, using the XbaI restriction enzyme, Multiple-Locus Variable-Number Tandem Repeat Analysis (MLVA) and plasmid profiles were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 36 publications
11
70
0
2
Order By: Relevance
“…In line with the current study findings, a study conducted by Mezal et al, showed that all isolates were positive for most of the virulence genes found in S. enterica (3).…”
Section: Discussionsupporting
confidence: 92%
“…In line with the current study findings, a study conducted by Mezal et al, showed that all isolates were positive for most of the virulence genes found in S. enterica (3).…”
Section: Discussionsupporting
confidence: 92%
“…Salmonella infection is one of the most critical bacterial diseases affecting poultry, resulting in a high mortality rate and production losses. Moreover, it is one of the most common foodborne bacterial diseases for humans worldwide, especially Salmonella enteritidis and Salmonella typhimurium [1], including more than 2600 serovars belonging to S. enterica which are Gram-negative and facultative anaerobes belonging to the family Enterobacteriaceae [2]. Cha et al [3] reported that Salmonella infection is widely distributed in poultry in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Послідовність праймерів Розмір фрагменту Автори invA 5'-TCATCGCACCGTCAAAGGAACC-3' 5'-GTGAAATTATCGCCACGTTCGGGCAA-3' 285 (Borges et al, 2013) agfB 5'-TGATGTTGACAATACTGGGTGCG-3' 5'-CGATATACTGGCATCGTTGGCAT-3' 293 Дане дослідження sefA 5'-GCCGTACACGAGCTTATAGA-3' 5'-ACCTACAGGGGCACAATAAC-3' 310 (Amini et al, 2010) Prt 5'-ATGGGAGCGTTTGGGTTC-3' 5'-CGCCTCTCCACTACCAACTTC-3' 624 (Hong et al, 2008) pFIA 5'-CCATGCTGGTTCTAGAGAAGGTG-3' 5'-GTATATCCTTACTGGCTTCCGCAG-3' 462 (Mezal et al, 2014) pN 5'-GTCTAACGAGCTTACCGAAG-3' 5'-GTTTCAACTCTGCCAAGTTC-3' 559 (Ahmed et al, 2006) pFIIA 5'-CTGTCGTAAGCTGATGGC-3' 5'-CTCTGCCACAAACTTCAGC-3' 270 (Mezal et al, 2014) tetG 5'-CAGCTTTCGGATTCTTACGG-3' 5'-GATTGGTGAGGCTCGTTAGC -3' 844 (Ahmed et al, 2006) Sul1 5'-GTGACGGTGTTCGGCATTCT -3' 5'-TGAGTGCATAACCACCAGCC -3' 378 (Ahmed et al, 2006) 5'-3'CS 5'-GGCATCCAAGCAGCAAGC-3' 5'-AAGCAGACTTGACCTGAT-3' 1009 (Ahmed et al, 2006) Результати та їх обговорення…”
Section: генunclassified